Health literacy and health seeking behavior among older men in a middle-income nation - Bourne, Paul A (Dove Medical Press, 2010)
Health literacy is a measure of the patient’s ability to read, comprehend and act on medical instructions. This research article examines health literacy and health-seeking behaviors among elderly men in Jamaica, in order to inform health policy. This is a descriptive cross-sectional study. A 133-item questionnaire was administered to a random sample of 2,000 men, 55 years and older, in St Catherine, Jamaica. In this study, 56.9% of urban and 44.5% of rural residents were health literate. Only 34.0% of participants purchased medications prescribed by the medical doctor and 19.8% were currently smoking. Despite the reported good self-related health status (74.4%) and high cognitive functionality (94.1%) of the older men, only 7.9% sought medical care outside of experiencing illnesses. Thirty-seven percent of rural participants sought medical care when they were ill compared with 31.9% of their urban counterparts. Thirty-four percent of the participants took the medication as prescribed by the medical doctor; 43% self-reported being diagnosed with cancers such as prostate and colorectal in the last 6 months, 9.6% with hypertension, 5.3% with heart disease, 5.3% with benign prostatic hyperplasia, 5.3% with diabetes mellitus, and 3.8% with kidney/bladder problems. Approximately 14% and 24% of the participants indicated that they were unaware of the signs and symptoms of hypertension and diabetes mellitus, respectively. The elderly men displayed low health literacy and poor health-seeking behavior. These findings can be used to guide the formulation of health policies and intervention programs for elderly men in Jamaica.